Neural cell adhesion molecule (NCAM) is the antigen recognized by monoclonal antibodies of similar specificity in small-cell lung carcinoma and neuroblastoma. - Patel, K; Moore, SE; Dickson, G; Rossell, R; Beverley, P; Kemshead, J; Walsh, F (1989)
We describe reagents from 2 workshops which had been identified as recognizing the same or very similar antigens based on their tissue reactivity. Examination of their tissue specificity led us to the conclusion that this was similar to the expression of the neural cell adhesion molecule (NCAM). We also describe the use of a transfection-based assay to show that these reagents do recognize NCAM. 3T3 cells were transfected with a full-length clone of human NCAM. Indirect immunofluorescence studies showed binding of all related antibodies to the transfectants, but not to the control 3T3 cells. In addition, biochemical analysis using certain antibodies in the cluster confirm that they detect NCAM in the transfectants. Our study shows the benefits of using workshops to compare monoclonal antibodies and a molecular approach to define the antigens recognized by such reagents.